Have Agile Techniques been the Silver Bullet for Software Development at Microsoft? - Murphy, Brendan; Bird, Christian; Zimmermann, Tom; Williams, Laurie; Nagappan, Nachi; Begel, Andrew (ACM ESEM, 2013)
Background. The pressure to release high-quality, valuable software products at an increasingly faster rate is forcing software development organizations to adapt their development practices. Agile techniques began emerging in the mid-1990s in response to this pressure and to increased volatility of customer requirements and technical change. Theoretically, agile techniques seem to be the silver bullet for responding to these pressures on the software industry. Aims. This paper tracks the changing attitudes to agile adoption and techniques, within Microsoft, in one of the largest longitudinal surveys of its kind (2006-2012). Method. We collected the opinions of 1,969 agile and non-agile practitioners in five surveys over a six-year period. Results. The survey results reveal that despite intense market pressure, the growth of agile adoption at Microsoft is slower than would be expected. Additionally, no individual agile practice exhibited strong growth trends. We also found that while development practices of teams may be similar, some perceive and declare themselves to be following an agile methodology while others do not. Both agile and non-agile practitioners agree on the relative benefits and problem areas of agile techniques. Conclusions. We found no clear trends in practice adoption. Non-agile practitioners are less enamored of the benefits and more strongly in agreement with the problem areas. The ability for agile practices to be used by large-scale teams generally concerned all respondents, which may limit its future adoption.